1980
DOI: 10.1007/bf00688530
|View full text |Cite
|
Sign up to set email alerts
|

Intranuclear aluminum content in Alzheimer's disease, dialysis encephalopathy, and experimental aluminum encephalopathy

Abstract: Nuclear and chromatin fractions were prepared from cerebral cortex of 34 human and 37 animal brains. Chromatin was separated into a heavy heterochromatin fraction and two euchromatin fractions: intermediate euchromatin and light euchromatin. Compared to age-matched controls, aluminum content expressed per gram of DNA was significantly increased in nuclear and heterochromatin fractions in pre-senile Alzheimer's disease. In contrast nuclear preparations from brains of patients who had died with dialysis encephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

1981
1981
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(49 citation statements)
references
References 24 publications
2
46
0
1
Order By: Relevance
“…15,[47][48][49][50] Increased aluminum content in the nuclei of AD neurons has been reported and it has been hypothesized in individuals predisposed to AD that aluminum enters neurons more readily, binds to their nuclei and accelerates cell death. 51 A follow-up study of miners subjected to aluminum dust as a putative prevention measure for silicosis in the MacIntyre mines in northern Ontario, has revealed an increased incidence of dementia in the miners so exposed. 52 Furthermore, aluminum levels in the local water supply appear to correlate with the incidence of AD in that location.…”
Section: Exposure To Neurotoxinsmentioning
confidence: 99%
“…15,[47][48][49][50] Increased aluminum content in the nuclei of AD neurons has been reported and it has been hypothesized in individuals predisposed to AD that aluminum enters neurons more readily, binds to their nuclei and accelerates cell death. 51 A follow-up study of miners subjected to aluminum dust as a putative prevention measure for silicosis in the MacIntyre mines in northern Ontario, has revealed an increased incidence of dementia in the miners so exposed. 52 Furthermore, aluminum levels in the local water supply appear to correlate with the incidence of AD in that location.…”
Section: Exposure To Neurotoxinsmentioning
confidence: 99%
“…The homology of linker histones to nuclear factor 1 (NF 1) suggest that the interaction of these DNA-binding proteins with specific DNA sequences may be a critical factor in the regulation of genetic processes such as transcription [5,6]. TGSDS-PAGE, Tris-glycine-SDS-polyacrylamide gel electrophoresis; PCA, perchloric acid; TAE, Tris-acetate-EDTA; LMG, low mobility group; A, adenine; T, thymine; BRL, Bethesda Research Laboratories Aluminum has been shown to accumulate in Alzheimer affected neocortical nuclei [7], possibly interacting with various components of the nuclear apparatus to disrupt genetic processes [8,9]. The presence of aluminum impairs salt-induced dissociation of linker histones from control nuclei preincubated with aluminum and the elution profile closely resembles that found for nuclei extracted from Alzheimer affected cerebral cortex [I0].…”
Section: Introductionmentioning
confidence: 99%
“…The aluminum hypothesis is controversial (Crapper McLachlan et al 1989, Doll 1993, Nieboer et al 1995): Alzheimer's disease has, though not undisputed (Wood et al 1988, Wettstein et al 1991, Landsberg et al 1992, been associated, on the one hand, with aluminum accumulation in the nuclear chromatin (Crapper et al 1980, Good et al 1992, in the neurofibrillary tangles Brody 1980, Good et al 1992) and focally in specific regions of the brain (Xu et al 1992) and, on the other hand, with aluminum in drinking water (Flaten 1986, Vogt 1986, Martyn et al 1989, Flaten 1990, Frecker 1991, Crapper McLachlan et al 1996.…”
mentioning
confidence: 99%